Pattern of dermatological disorders seen in skin biopsy material from the Central Province, Sri Lanka, with special reference to Histopathology - Babapulle, M (My University, 1983)
The pattern of dermatological disorders as seen in 110 skin biopsies of patients from the central province Sri Lanka in a one year period (1982/1983) was studied with reference to incidence, age, sex ,race and clinical and histopathological features. The commonest disorders observed in biopsies were lichen amyloidosus, skin tumours,leprosy and collagen diseases. Viral and fungal diseases were only very rarely seen. Skin disorders in general were commoner in females, and rare in the very old and very young. Facilities required for proper and complete laboratory investigation of dermatological cases are suggested